Authentic sheep meat in the European Union: Factors influencing and validating its unique meat quality. (13th February 2017) - Erasmus, Sara W; Muller, Magdalena; Hoffman, Louwrens C
Abstract: Authentic meat products are gaining attention through their unique quality characteristics linked to their origin. Various factors are known to influence the quality of fresh meat. This review describes the different Protected Designation of Origin (PDO) and Protected Geographical Indication (PGI) lamb types and discusses the factors which influences its unique sensory and chemical characteristics. Flavour, aroma, texture and colour play an integral part in the sensory quality of denomination of origin fresh meat products. For authentic fresh sheep meat the sensory (as well as chemical) quality is largely influenced by diet followed by breed, age and gender. However, diet forms the link with the geographical area of origin, which together with the traditional production system and sheep breeds used, lends the product its authentic nature. This review shows how diet linked to origin can affect the quality of the meat and furthermore how other factors such as breed can also have an effect. Research relating to the authentic lamb types were evaluated and the shortcomings highlighted in order to assist with the development of PDO and PGI specifications in the future. © 2016 Society of Chemical Industry